On Experience and Psychotherapy A Dialogue with Michel de Montaigne (Existential Analysis: Journal of the Society for Existential Analysis, 2007)
This paper concerns itself with the relevance of Montaigne's writings for the practice of contemporary psychotherapy. Montaigne demands a personal investment from his readers beyond the scope of analytic philosophy as it is often presented. For this reason, a brief exploration of the historical significance of Montaigne is followed by an account of my personal dialogue with his text On Experience. In adopting this philosophical and literary style, I have attempted to tease out some of the issues I consider relevant to my own psychotherapeutic practice and which, it is hoped, might also be relevant to others aligning their practice along existential-phenomenological principles.